Cancer Predisposition Syndromes Associated With Pediatric High-Grade Gliomas - Giulia Ceglie; Giada Del Baldo; Emanuele Agolini; Martina Rinelli; Antonella Cacchione; Francesca Del Bufalo; Maria Vinci; Roberto Carta; Luigi Boccuto; Luigi Boccuto; Evelina Miele; Angela Mastronuzzi; et al. (Frontiers Media S.A., 2020)
Pediatric High-Grade Gliomas (pHGG) are among the deadliest childhood brain tumors and can be associated with an underlying cancer predisposing syndrome. The thorough understanding of these syndromes can aid the clinician in their prompt recognition, leading to an informed genetic counseling for families and to a wider understanding of a specific genetic landscape of the tumor for target therapies. In this review, we summarize the main pHGG-associated cancer predisposing conditions, providing a guide for suspecting these syndromes and referring for genetic counseling.